PRECLINICAL EVALUATION OF NANOMATERIAL-BASED THERAPEUTICS FOR TRANSLATIONAL MEDICINE - Ryan Teo; Ethan Tan; Ava Lee (Yayasan Adra Karima Hubbi, 2026)
Nanomaterial-based therapeutics have shown immense promise in translational medicine, offering innovative solutions for targeted drug delivery, cancer therapy, and regenerative medicine. The unique properties of nanomaterials, including their high surface area, biocompatibility, and ability to be engineered for specific functions, make them ideal candidates for improving the precision and efficacy of medical treatments. However, the preclinical evaluation of these nanomaterials is critical to ensuring their safety, efficacy, and clinical applicability. This study aims to evaluate the preclinical performance of nanomaterial-based therapeutics in the context of translational medicine. The research focuses on assessing the pharmacokinetics, biocompatibility, and therapeutic efficacy of nanomaterials in animal models to determine their potential for clinical translation. A series of preclinical tests were conducted using animal models to assess the pharmacokinetics, biodistribution, and toxicity of various nanomaterials. Therapeutic efficacy was evaluated through specific disease models, including cancer and wound healing, using both in vitro and in vivo techniques. The study demonstrated that nanomaterial-based therapeutics exhibited promising pharmacokinetics and high therapeutic efficacy, with minimal toxicity. Nanomaterials showed targeted drug delivery and enhanced therapeutic outcomes in preclinical models, particularly in cancer therapy. Nanomaterial-based therapeutics hold significant potential for advancing translational medicine. Preclinical evaluations confirm their promise for targeted therapy, though further research on long-term safety and clinical translation is needed.